Regions of broad-host-range plasmid RK2 which are essential for replication and maintenance. - Thomas, C M (1980)
The sites of cleavage on the map of the broad-host-range plasmid RK2 (56 kilobases) were determined for the BglII, PstI, and SmaI restriction enzymes, and the determinants for tetracycline and ampicillin resistance were localized. The cleavage sites were clustered at or near the drug resistance genes. To localize regions required for plasmid replication and maintenance in Escherichia coli, we deleted nonessential regions of RK2 by partial digestion with the restriction endonuclease HaeII to produce small derivatives. The smallest stable replicon obtained contained five HaeII fragments of RK2 which total 5.4 kilobases. These fragments were derived from three regions of RK2 that are separated from each other by antibiotic resistance genes. One of these HaeII fragments (0.75 kilobases) has the properties expected of the origin of replication. The outer four fragments, located in two separate regions of RK2, were found to provide, in trans, functions that permit the replication of the HaeII fragment carrying the origin of the replication. These results indicate that at least two plasmid-encoded genes, capable of acting in trans, and a replication origin are required for RK2 replication and maintenance.